Predictors of increased melphalan exposure correlate with overall survival, nonrelapse mortality, and toxicities in patients undergoing reduced-intensity allogeneic stem cell transplantation with fludarabine and melphalan. (April 2021) - Sweiss, Karen; Calip, Gregory Sampang; Holden, Jaime; Lewkowski, Paulina; Mialik, Iryna; Johnson, Jeremy; Galvin, John P; Rondelli, Damiano; Patel, Pritesh
The reduced-intensity conditioning regimen, fludarabine and melphalan 140 mg/m 2 (FM140), is widely adopted in practice. Pharmacokinetic studies report 10-fold interpatient variability in melphalan exposure. We identified low hemoglobin (Hb) and/or creatinine clearance (CrCl), determinants of melphalan pharmacokinetic, as strong predictors of outcomes after high-dose melphalan and autologous transplant. We hypothesized that these variables could predict for outcomes after FM140. Overall survival was shorter in patients with a lower Hb (113 vs. 2536 days; p  = 0.004), due to an increased rate of nonrelapse mortality (NRM) ( p  = 0.0005). Overall survival was also worse in patients with lower CrCl (75 vs. 317 days; p  = 0.003), with a significantly worse nonrelapse mortality ( p  = 0.0023). In a multivariate analysis, a higher Hb and CrCl predicted for better overall survival ( p  = 0.017). In patients with a lower Hb, the median duration of hospitalization ( p  = 0.02) and the mean duration of diarrhea ( p  = 0.008) were longer. In patients with a lower CrCl, the median duration of hospitalization ( p  = 0.06) and the mean duration of diarrhea ( p  = 0.0009) longer, and the rate of infection was higher ( p  = 0.02). We show for the first time that Hb and CrCl represent important determinants of outcomes after FM140, suggesting that pharmacokinetic-directed dosing may be beneficial in achieving optimal outcomes.